Sifat Penyerapan Lembab Bubuk Buah Durian dan Sirsak - Suyitno T. (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1995)
Moisture sorption characteristics of durian and soursop fruit powder were studied. Durian and soursop fruit powder moisture sorption isotherm data were best fitted with cubic polynomial equation curve. Soursop fruit powder was more hygroscopic then durian powder. The primary, secondary and tertiary bound water zone of durian and soursop fruit powder were located at a.: 0 - 030, 030-0.58, and 0.58 - 1.0, respectively. The critical moisture content of durian and soursop fruit powder, i.e. M.-BET, Mp, M., and ni; were decreased with increasing temperature. ,